Genistein improves the reproductive performance and bone status of breeder hens during the late egg-laying period. (15th July 2019) - Lv, Z P; Yan, S J; Li, G; Liu, D; Guo, Y M
ABSTRACT: Genistein (GEN), a type of soy isoflavones, is similar to estrogen structurally and functionally. The effects of dietary gen on the reproductive performance and bone status of breeder hens were investigated. A total pf 720 laying broiler breeder (LBB) hens were randomly allocated into 3 groups with supplemental dietary GEN doses (0, 40, 400 mg/kg). Each treatment has 8 replicates of 30 birds. The results indicated that supplemental GEN significantly improved the egg production and eggshell strength of LBB hens. Dietary GEN was deposited into the egg yolk, which decreased malonaldehyde in the follicle and egg yolk. The levels of vitellogenin (VTG ), progesterone, and follicle-stimulating hormone in the serum of GEN-treated groups were elevated compared with the control group. Furthermore, GEN treatment downregulated the mRNA expression of insulin-like growth factor binding protein in the fallopian tube, whereas 40 mg/kg GEN treatment upregulated estrogen receptor α expression. Both the mRNA expression of VTG-II in the liver and mRNA expression of amphiregulin in the fallopian tube were upregulated after 40 and 400 mg/kg GEN treatment. In the 400 mg/kg GEN-treated group, the levels of calcitonin and alkaline phosphatase in the serum were increased compared with the control group, which was consistent with the increased levels of calcium and phosphorus in the tibia. Supplemental GEN (400 mg/kg) improved the tibia strength of LBB hens, whereas 40 mg/kg GEN had better effects on laying performance. In summary, dietary GEN could improve the egg production and quality, as well as the bone status of LBB hens during the late egg-laying period.